Formulasi Gel Anti Luka Berbahan Baku Putih Telur Ayam Ras Terhadap Luka Sayatan pada Mencit (Mus Musculus) - A. Rufaidah Hashary; Alhidayatullah Alhidayatullah; Febi Miranti Saputri (Universitas Borneo Lestari, 2022)
Egg whites can traditionally be used for wound treatment. Egg white is formulated in the form of a gel to make it easy to apply and cover the characteristic odor of egg whites. The purpose of the study was to determine whether egg whites could be made in the form of wound liver gel and to find out at what concentration egg whites were better at healing wounds. The research method was carried out experimentall. The egg white gel formula was made in two concentrations, namely 50% and 60%, besides that the positive control used was Bioplacenton while the negative control was without treatment. The results of wound healing in the positive control treatment and the 60% egg white gel treatment had almost the same wound healing rate, while the gel that gave the better healing effect was the 50% egg white gel treatment.